1999
DOI: 10.1021/es980636e
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Dimethyloligosulfides in Lake Kinneret:  Biogenic Formation of Inorganic Oligosulfide Intermediates under Oxic Conditions

Abstract: The mechanism of formation of dimethyloligosulfides in Lake Kinneret was investigated by field and laboratory studies. The process was simulated under laboratory conditions using obligate aerobic and facultative bacteria that were isolated from Lake Kinneret and fed with different types of organo-sulfur nutrients. The lysis products of Peridinium gatunensea dinoflagellate that dominates the phytoplankton population in Lake Kinneret during the winter−spring seasonare the primary source of dimethyloligosulfide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 35 publications
2
26
0
1
Order By: Relevance
“…Ginzburg et al, 1999;Gun et al, 2000). Because of their extremely strong and offensive odors, it is not likely that higher concentrations of unknown S 0 -org V compounds exist but have been overlooked.…”
Section: Analytes Contributing To Rss Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ginzburg et al, 1999;Gun et al, 2000). Because of their extremely strong and offensive odors, it is not likely that higher concentrations of unknown S 0 -org V compounds exist but have been overlooked.…”
Section: Analytes Contributing To Rss Measurementsmentioning
confidence: 99%
“…Ginzburg et al (1999) showed that this mechanism produces <<1 nM of inorganic and organic polysulfides in the oxic waters of Lake Kinneret. However, the polysulfides identified in Lake Kinneret are much less abundant than RSS NV in Rogoznica Lake, and they vary vertically and seasonally in a manner that clearly implicates a phytoplankton source.…”
Section: Seasonal Behavior Of Rss Tnvmentioning
confidence: 99%
“…At micromolar or higher concentrations of sulfide, polysulfidic zero-valent sulfur compounds -together with dissolved cyclooctasulfur -constitute the main dissolved zero-valent sulfur pools in natural aquatic systems (Boulegue, 1978;. Polysulfides have been implicated in a number of important geochemical reactions, such as pyritization (Rickard, 1975;Howarth, 1979;Luther, 1991;Chadwell et al, 1999;Luther and Rickard, 2005) and organic sulfur compounds formation (Aizenshtat et al, 1983;Kohnen et al, 1989;Vairavamurthy and Mopper, 1989;Vairavamurthy et al, 1992;Krein and Aizenshtat, 1993;Amrani and Aizenshtat, 2004;Ginzburg et al, 1999;Heitz et al, 2000;Kamyshny et al, 2003a;Werne et al, 2008). Moreover, zero-valent sulfur compounds act as key intermediates in the oxidative half of the microbial sulfur cycle, (Zopfi et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Polysulfides play an important role in numerous environmental processes due to their high reductive and nucleophilic reactivity. Among those processes are transition metal complexation and pyrite formation (Rickard 1975;Howarth 1979;Luther 1991;Paquette and Helz 1997;Chadwell et al 1999;Luther and Rickard 2005), thiosulfate production by disproportionation to sulfide and thiosulfate under basic conditions (Bloxam 1895;Giggenbach 1974;Licht and Davis 1997), sulfurization of sedimentary organic matter (Aizenshtat et al 1983;Kohnen et al 1989;Vairavamurthy and Mopper 1989;Vairavamurthy et al 1992;Krein and Aizenshtat 1993;Aizenshtat et al 1995;Amrani and Aizenshtat 2004), volatile sulfur compounds (VSCs) formation (Ginzburg et al 1999;Heitz et al 2000;Franzmann et al 2001;Kamyshny et al 2003), as well as reductive dehalogenation and nucleophilic substitution of organo-halogen pollutants (Roberts et al 1992;Perlinger et al 1996;Miller et al 1998;Lippa and Roberts 2002;Loch et al 2002).…”
Section: Introductionmentioning
confidence: 99%